The rough guide to Vietnam - Dodd, Jan; Lewis, Mark (London Rough Guides, 2000)
Contents: Basics; the guide: Ho Chi Minh city and around; the Mekong delta; the southern and central highlands; the south-central coast; the central provinces; Hanoi and around; Ha Long bay and the northern seaboard; the far north,...
Keywords: Quản trị DV Du lịch và Lữ hành